Perfectionism, efficacy, and daily coping and affect in depression over 6 months. Issue 6 (2nd November 2020) - Richard, Alexandra; Dunkley, David M.; Zuroff, David C.; Moroz, Molly; Elizabeth Foley, J.; Lewkowski, Maxim; Myhr, Gail; Westreich, Ruta
Abstract: Objective: This study examined how perfectionism and efficacy impacted the maintenance of daily coping and affect in depression over six months. Method: Forty‐six depressed patients (69.6% female, mean age = 41.11 years) completed measures of perfectionism dimensions (self‐critical, personal standards), efficacy, and depressive severity at Time 1. Participants then completed daily diaries of stress appraisals, coping, and affect for 7 consecutive days at Time 1 and Time 2, 6 months later. Results: Perfectionism dimensions and efficacy were differentially correlated with appraisals, coping, and affect across Times 1 and 2. Behavioral disengagement tendencies mediated the relation between self‐critical perfectionism and daily negative affect over 6 months, controlling for depressive severity. Efficacy was related to daily positive affect over 6 months through problem‐focused coping tendencies. Conclusions: Results highlight the importance of addressing perfectionism, efficacy, and daily coping tendencies to more effectively reduce distress and bolster resilience in people with depression.